Prospective associations between child screen time and parenting stress and later inattention symptoms in preschoolers during the COVID-19 pandemic - Almeida, Maíra Lopes; Garon-Carrier, Gabrielle; Cinar, Eda; Frizzo, Giana Bitencourt; Fitzpatrick, Caroline (Frontiers in Psychology, 2023)
Child attention skills are critical for supporting self-regulation abilities, especially during the first years of life. On the other hand, inattention symptoms in preschoolers have been associated with poor school readiness, literacy skills and academic achievement. Previous research has linked excessive screen time with increased inattention symptoms in early childhood. However, most research has only focused on TV exposure and did not investigate this association during the COVID-19 pandemic. This atypical context has increased screen time in children worldwide, including preschoolers. This study aimed to investigate the prospective association between child screen time and parenting stress when children were 3.5 and later inattention symptoms at age 4.5. Participants were parents of Canadian preschoolers that reported screen media use, parenting stress, and individual child and family characteristics during the pandemic (N=315, 2020) and inattention symptoms one year later (N=264). Analyses using multiple linear regression, revealed a positive association between child screen time at age 3.5 and inattention symptoms at 4.5 years. Parental stress was also positively associated with child inattention symptoms. Associations were observed above individual (child age, inhibitory control, and sex) and family (parent education and family income) characteristics. These results highlight that preschooler screen use and parenting stress may undermine attentional skills. Practical implications are discussed.